Scalability, test–retest reliability and validity of the Brief INSPIRE-O measure of personal recovery in psychiatric services - Moeller, Stine Bjerrum; Larsen, Pia Veldt; Austin, Stephen; Slade, Mike; Arendt, Ida-Marie T. P.; Andersen, Martin Stolpe; Simonsen, Sebastian (Frontiers in Psychiatry, 2024)
Introduction Mental health services have transitioned from treating symptoms to emphasizing personal recovery. Despite its importance, integrating personal recovery into clinical practice remains work in progress. This study evaluates the psychometric qualities of the Brief INSPIRE-O, a five-item patient-reported outcome measure assessing personal recovery. Method The study collected data from 2018 to 2020 at the Mental Health Services, Capital Region of Denmark, using an internet-based system examining 8,192 non-psychotic patients – receiving outpatient treatment. Materials This study evaluated the Brief INSPIRE-O and used measures of symptomatology (SCL-10), well-being (WHO-5), and social functioning (modified SDS). Results The study population comprised 76.8% females with a mean age of 32.9 years, and diagnoses included anxiety (28%), depression (34%), and personality disorder (19%). The mean Brief INSPIRE-O score (39.9) was lower than the general population norm (71.1). The Brief INSPIRE-O showed acceptable test–retest reliability (0.75), scalability (0.39), and internal consistency (0.73). Correlations with other mental health criteria were in the expected direction for symptomatology (−0.46), well-being (0.60), and social functioning (−0.43) and remained consistent across diagnoses. Discussion The Brief INSPIRE-O demonstrated strong psychometric qualities and could be recommended as a measure of personal recovery for use in both research and clinical practice. Its strong theoretical basis and short completion time make it suitable for use for research. Incorporating Brief INSPIRE-O into clinical assessment will further support the process of mental health systems re-orientating towards personal recovery.